PREPARING DECISION REGARDING LAMPUNG SOLAR PRINTING BANNER MAKING SERVICES USING MARKETING MIX (7P) - Yulianti, Nanda; Imam, Khairul; Abdullah, Agung (Journal of Management Small and Medium Enterprises (SMEs), 2025)
A particular emphasis will be placed on the banner manufacturing service that Surya Printing Lampung offers to accomplish the purpose of this research, which is to investigate the influence of the promotion mix (7P) on the purchasing decision of consumers. A total of 96 samples, as part of this investigation, were used to perform multiple regression. The assistance of SPSS version 23 was used. According to the obtained regression analysis, factors such as value, position, location, and procedures, as well as physical evidence, have a favorable and significant impact through statistics on retail customers' purchasing decision. Off-product and people variables, on the other hand, do not provide evidence of such a link. While this is going on, the marketing mix (7P), which is determined by the F test, is affecting the decision to purchase banner manufacturing services from Surya Printing Lampung. Keywords: Purchasing Decision ;Marketing Mix (7P); Banner